2008
DOI: 10.1111/j.1442-200x.2008.02635.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant injuries from child restraint safety seat misuse at British Columbia Children’s Hospital

Abstract: Injury prevention efforts should be focused on reducing CRS outside the motor vehicle setting and preventing placement of the CRS at an elevated surface. Educating caregivers on the dangers of falls resulting from CRS misuse in a variety of care settings is also recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…[128][129][130][131][132] In addition, there is increasing concern about injuries from falls resulting from car seats being placed on elevated surfaces. [133][134][135][136][137] An analysis of CPSC data revealed 15 suffocation deaths between 1990 and 1997 resulting from car seats overturning after being placed on a bed, mattress, or couch. 136 The CPSC also warns about the suffocation hazard to infants, particularly those who are younger than 4 months, who are carried in infant sling carriers.…”
Section: Car Seats and Other Sitting Devices Are Not Recommended For mentioning
confidence: 99%
“…[128][129][130][131][132] In addition, there is increasing concern about injuries from falls resulting from car seats being placed on elevated surfaces. [133][134][135][136][137] An analysis of CPSC data revealed 15 suffocation deaths between 1990 and 1997 resulting from car seats overturning after being placed on a bed, mattress, or couch. 136 The CPSC also warns about the suffocation hazard to infants, particularly those who are younger than 4 months, who are carried in infant sling carriers.…”
Section: Car Seats and Other Sitting Devices Are Not Recommended For mentioning
confidence: 99%
“…Car safety seats and similar products are not stable on a crib mattress or other elevated surfaces. [25][26][27][28][29] 3. Room-sharing without bedsharing is recommendedThere is evidence that this arrangement decreases the risk of SIDS by as much as 50%.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, parents rely on health professionals for up-to-date accurate information on child health, health promotion and child safety. Research demonstrates that one-on-one education is effective in preventing injuries (19). In our opinion, one-on-one child safety educational programmes should start immediately after birth, with the in-hospital medical team identifying parents who need individual guidance and different methods of information delivery.…”
Section: Discussionmentioning
confidence: 95%
“…Research demonstrates that one-on-one education is effective in preventing injuries (19). Desapriya et al (19) demonstrated the importance of injury-prevention education during routine health maintenance visits to primary care physicians. The educational content provided to parents should include CSS use and other important topics on child safety, such as CSS quality standards and CSS safety outside the car (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation